Introduction to Real-Time Signal Processing Algorithms for 5G and Beyond: Beamforming and Channel Estimation Strategies - Idris, Olayinka Oduola (Darul Yasin Al Sys, 2025)
The emergence of 5G and the exploration of beyond-5G (B5G) and 6G networks have introduced new paradigms in wireless communication, characterized by ultra-high data rates, massive connectivity, and ultra-low latency. Real-time signal processing has become a critical enabler of these technologies, particularly in the areas of beamforming and channel estimation. Beamforming enables the focused transmission of signals, improving signal strength and reducing interference, while channel estimation provides essential knowledge of the transmission environment, allowing for dynamic adaptation of communication strategies. This paper provides a comprehensive review of beamforming and channel estimation strategies in 5G, with a focus on their real-time implementation. It explores various types of beamforming—analog, digital, and hybrid—as well as channel estimation methods including pilot-based, blind, and semi-blind techniques. The integration of these methods is also examined, along with real-time algorithmic approaches such as LMS, RLS, Kalman filtering, and machine learning models. Applications across massive MIMO, millimeter-wave communication, and vehicular networks are discussed. Finally, the paper outlines future research directions, emphasizing the growing role of AI, machine learning, and emerging quantum computing technologies in optimizing real-time signal processing for 6G and beyond.